Identification of Malaria Parasites in Chasan Boesoirie General Hospital Ternate East Nusa Tenggara - Desto Arisandi; Sofvirah R. Sohy; Fitri Nadifah (LPPM STIKES Guna Bangsa, 2016)
Background: Malaria is still a global health problem especially in tropical countries, such as Indonesia. Based on survey 35% of the Indonesia population were live in endemic areas of malaria, such as Provinces of Maluku, North Maluku, Papua, West Papua, North Sumatra, and East Nusa Tenggara. Malaria is caused by a mosquito bite of female Anopheles sp. containing Plasmodium parasite. Generally it bites humans at night or dawn. Such malaria parasites are Plasmodium falciparum, Plasmodium vivax, Plasmodium malariae, and Plasmodium ovale. Malaria is a disease of both highest in Ternate and mostly occur in general hospitals of Chasan Boesoirie General Hospital. This research aims to identify the type of malaria parasites in the Chasan Boesoirie General Hospital Ternate. Method: This is a descriptive research conducted in Chasan Boesoirie General Hospital in Ternate, East Nusa Tenggara in March 2015. Research data obtained include: age, sex, education, and employment. Identification of malaria is carried out based on an examination of the existence of Plasmodium in preparation of thin and thick blood apus. Descriptive analysis using STATA programs for Windows version 12.0 (Stata Corp LP., College Station, TX, USA) are presented in the form of tables and narratives. Result: This research subjects were 69 people suspected with malaria infection. Suspected malaria to be infected by Plasmodium is more are young age group 94%, 88% were males, 100% have a poor education or un-educated, as well as the of 100% were fishermen. As much as 54 people (78%) were infected by Plasmodium parasites consisting of Plasmodium falcifarum 48 people (89%) and Plasmodium vivax 6 people (11%). Conclusion: The incidence of malaria infections in Chasan Boesoirie General Hospital amounted to 78% and the type of infected parasites were Plasmodium falcifarum and Plasmodium vivax.